2019
DOI: 10.1063/1.5109025
|View full text |Cite
|
Sign up to set email alerts
|

Defects at the surface of β-Ga2O3 produced by Ar plasma exposure

Abstract: Films of β-Ga2O3 grown by halide vapor phase epitaxy on native substrates were subjected to Ar inductively coupled plasma treatment. As a result, the built-in voltage of Ni Schottky diodes deposited on the plasma treated surfaces decreased from 1 V to −0.02 V due to the buildup of deep trap concentration in the near surface region. Deep level spectra measurements indicate a strong increase in the top ∼200 nm of the plasma treated layer of the concentration of E2* (Ec − 0.8 eV) and especially E3 (Ec − 1.05 eV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…We observed slightly higher resistance and Schottky behavior of exfoliated n-Ga 2 O 3 +etching sample compared with the as-grown n-Ga 2 O 3 /mica. This phenomenon could be attributed to (i) material quality difference between the top n-Ga 2 O 3 layer and exfoliated bottom n-Ga 2 O 3 , which may contain polycrystal interfacial layer, , and (ii) plasma damages after Ar dry etching. , …”
Section: Resultsmentioning
confidence: 99%
“…We observed slightly higher resistance and Schottky behavior of exfoliated n-Ga 2 O 3 +etching sample compared with the as-grown n-Ga 2 O 3 /mica. This phenomenon could be attributed to (i) material quality difference between the top n-Ga 2 O 3 layer and exfoliated bottom n-Ga 2 O 3 , which may contain polycrystal interfacial layer, , and (ii) plasma damages after Ar dry etching. , …”
Section: Resultsmentioning
confidence: 99%
“…This effect is shown in Figures a,b, where it is observed that the traps had a negligeable effect in contrast with our previous study, where these traps have a pronounced effect at higher temperatures (greater than 300 K). This result is due to the high electron concentration on the surface of Si-doped β-Ga 2 O 3 and the tunneling current domination in addition to the fact that a higher temperature results in more activated traps …”
Section: Resultsmentioning
confidence: 99%
“…This result is due to the high electron concentration on the surface of Sidoped β-Ga 2 O 3 and the tunneling current domination in addition to the fact that a higher temperature results in more activated traps. 8 Temperature-Dependent SBD Current. Now, the temperature dependence of the J−V characteristics and comparison with measurement for the mentioned model are carried out, as shown in Figure 8.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure c shows the summarized Arrhenius space of the majority carrier traps in this work and refs and . The DLTS peaks at 310, 350, and 410 K have been assigned to the E2* traps related to intrinsic defects (V Ga or V Ga –V O ), the unintentional doped impurity E2 traps related to Fe substituting for Ga (Fe Ga ), and E3 traps in the HVPE-grown β-Ga 2 O 3 , respectively. , Table summarizes the detailed trap parameters. The E3 trap has been reported to be related to surface contaminants (e.g., Ti, Fe, and Co) with an energy level of E C – 1.09 eV and a capture cross section of σ E3 = 4.30 × 10 –14 cm 2 , which are completely removed by the dry etching, together with the reduced E2 trap ( E C – 0.83 eV and σ E2 = 2.56 × 10 –15 cm 2 ) in concentration ( N TE2 ).…”
mentioning
confidence: 81%